Corporate Social Responsibility and the Sustainable Competitive Advantage - Dumitru Miron; Monica Petcu; Iulia Maria Sobolevschi (Amfiteatru Economic Journal, 2011)
Being currently under the pressure of the various imbalances induced in the natural and social environment and faced with the deficiency of its own incremental growth, the economic system – which is exclusively focused on the economic performance – is currently going through a stage of global structural changes meant to connect it to the simple values of the community, society and even humanity as a requirement for its survival and development through the sustainable competitive advantage. Taking into consideration that globalization tends to quickly standardize technologies and to equalize the rates of profits, the area of competitive advantage is extended beyond the area of economic factors (product differentiation, cost reduction, etc.) in interferential areas, where factors such as social responsibility assumed by corporations become levers to increase competitiveness. Corporate social responsibility circumscribes the company's set of obligations to the stakeholders (individuals, groups or organizations that are directly or indirectly affected by the actions, goals and policies of the corporation) in a certain system of reference. The multiple groups that make up the reference society of a corporation lead to a multitude of expectations. The legitimacy of these expectations embraces various degrees of validity. Responsibility is a continuous dynamic process meant to harmonize and balance the interests of various groups and the roles they play in relation to and for the purpose of the common good. So far, no system of indicators has been unanimously accepted and no methodology has been crystallized for measuring the effect of the social effort made in the sphere of social responsibility. Nevertheless, research performed over the past years has shown that an ethical behaviour involved in the issues of the natural, social and business environment has an obvious positive influence on the reputation and sales of the corporations. The corporations' competitive strategies should include – apart from specific goals such as market share, product differentiation or smart promotion – the goal of harmonizing stakeholder expectations. In this context, the commitment to social responsibility becomes an important pillar in gaining the partners' and the public's confidence, along with a recognition that would strengthen the company's market position and its commitment to a competitive sustainable approach.
Keywords: D01; D60; 330; responsibility; social performance; sustainability; competitive advantage